Vertical control in the Class III compensatory treatment - Márcio Costa Sobral; Fernando A. L. Habib; Ana Carla de Souza Nascimento (Dental Press Editora, 2013)
INTRODUCTION: Compensatory orthodontic treatment, or simply orthodontic camouflage, consists in an important alternative to orthognathic surgery in the resolution of skeletal discrepancies in adult patients. It is important to point that, to be successfully performed, diagnosis must be detailed, to evaluate, specifically, dental and facial features, as well as the limitations imposed by the magnitude of the discrepancy. The main complaint, patient's treatment expectation, periodontal limits, facial pattern and vertical control are some of the items to be explored in the determination of the viability of a compensatory treatment. Hyperdivergent patients who carry a Class III skeletal discrepancy, associated with a vertical facial pattern, with the presence or tendency to anterior open bite, deserve special attention. In these cases, an efficient strategy of vertical control must be planned and executed. OBJECTIVE: The present article aims at illustrating the evolution of efficient alternatives of vertical control in hiperdivergent patients, from the use, in the recent past, of extra-oral appliances on the lower dental arch (J-hook), until nowadays, with the advent of skeletal anchorage. But for patients with a more balanced facial pattern, the conventional mechanics with Class III intermaxillary elastics, associated to an accentuated curve of Spee in the upper arch and a reverse Curve of Spee in the lower arch, and vertical elastics in the anterior region, continues to be an excellent alternative, if there is extreme collaboration in using the elastics.